(untitled) (Current Horticulture, 2024)
Majority of farmers growing tubers and spices are small and marginal ores. They are resource poor and predominantly rainfed farmers. Initial investments on planting material of these crops are too high. In an effort to help them to overcome these uncertainties of crop losses due to weather and disease, the present research on growing tubers and spices in used polypropylene bags was done. The productivity was double to that of traditional cultivation practices.